2019
DOI: 10.1002/pd.5550
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of chromosomal aberrations by chromosomal microarray analysis in fetuses with ultrasound anomalies in the urinary system

Abstract: Objectives This study aimed to explore the relationships between urinary anomalies and copy number variations (CNVs) in fetuses and provide information for prenatal diagnosis and genetic counseling for parents. Methods Three hundred seventeen fetuses with urinary system anomalies detected by prenatal ultrasound were enrolled; 251 had isolated urinary system anomalies, and 66 had nonisolated system anomalies. CMA was performed on the Affymetrix 750K platform. Results The frequency of chromosomal aberrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…Whole genomic DNA was extracted from peripheral blood cells of each patient and his or her parents using QIAamp DNA Blood Mini Kit (Qiagen, Valencia, CA, USA) and subjected to CMA-single nucleotide polymorphism (SNP) array analysis by using the Affymetrix® CytoScan™ 750K Array (Affymetrix, Santa Clara, CA, USA). The procedure was described in our previous publication [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole genomic DNA was extracted from peripheral blood cells of each patient and his or her parents using QIAamp DNA Blood Mini Kit (Qiagen, Valencia, CA, USA) and subjected to CMA-single nucleotide polymorphism (SNP) array analysis by using the Affymetrix® CytoScan™ 750K Array (Affymetrix, Santa Clara, CA, USA). The procedure was described in our previous publication [13].…”
Section: Methodsmentioning
confidence: 99%
“…The detected CNVs were systematically evaluated for clinical significance. The procedure was also described in our previous publication [13].…”
Section: Methodsmentioning
confidence: 99%
“…Aneuploidies/polyploidy or P/LP CNVs (n(%)) VUS (n(%)) Normal (n(%)) www.nature.com/scientificreports/ subsequently subjected to SNP array analysis using the CytoScan 750 K Array (Thermo Fisher Scientific, Santa Clara, CA, USA). The procedures were conducted according to the manufacturers' instructions with 250 ng of gDNA, as described in our previous publication 36 . The molecular karyotype analysis was performed using Chromosome Analysis Suite (ChAS) v4.1 (ThermoFisher Scientific).…”
Section: Totalmentioning
confidence: 99%
“…Results including etiology, associated anomalies, outcome and available follow-up are shown in Table 2. There were 114 nonisolated cases documented in the literature 9,17,18 which are combined with our cohort and shown in Figure 1CD Although there are no current prenatal guidelines for the testing of pregnancies with isolated fetal HE, recent work by Lei et al has shown that approximately 20% (4/20 cases, two of ADPKD, one of Tubular Dysgenesis and one of HNF1B-related disorders) of cases may have pathogenic variants identified on whole exome sequencing. 21 The same group reported additional cases (two of Meckel-Gruber, two of BBS, one of osteogenesis imperfecta type II, and one of renalhepatic-pancreatic dysplasia) with multisystem involvement including HEK.…”
Section: Provincial Cohort and Literature Reviewmentioning
confidence: 81%
“…Our literature search yielded 116 studies, of which six case series studies were included. 8,[10][11][12]17 These studies included a total of 204 cases of isolated HE. In combining the isolated cases of fetal HEK from both the literature and our data there are a total of 224 cases presented in Figure 1AB.…”
Section: Isolated Casesmentioning
confidence: 99%